Comparison of Nested Polymerase Chain Reaction and Real-Time Polymerase Chain Reaction with Parasitological Methods for Detection of Strongyloides stercoralis in Human Fecal Samples - Sharifdini, Meysam (Am J Trop Med Hyg, 2015)
This study was performed to evaluate nested polymerase chain reaction (PCR) and real-time PCR methods for detection of Strongyloides stercoralis in fecal samples compared with parasitological methods. A total of 466 stool samples were examined by conventional parasitological methods (formalin ether concentration [FEC] and agar plate culture [APC]). DNA was extracted using an in-house method, and mitochondrial cytochrome c oxidase subunit 1 and 18S ribosomal genes were amplified by nested PCR and real-time PCR, respectively. Among 466 samples, 12.7% and 18.2% were found infected with S. stercoralis by FEC and APC, respectively. DNA of S. stercoralis was detected in 18.9% and 25.1% of samples by real-time PCR and nested PCR, respectively. Considering parasitological methods as the diagnostic gold standard, the sensitivity and specificity of nested PCR were 100% and 91.6%, respectively, and that of real-time PCR were 84.7% and 95.8%, respectively. However, considering sequence analyzes of the selected nested PCR products, the specificity of nested PCR is increased. In general, molecular methods were superior to parasitological methods. They were more sensitive and more reliable in detection of S. stercoralis in comparison with parasitological methods. Between the two molecular methods, the sensitivity of nested PCR was higher than real-time PCR.